Convergent Validity of Three Methods for Measuring Postoperative Complications. (June 2016) - Fritz, Bradley A.; Escallier, Krisztina E.; Ben Abdallah, Arbi; Oberhaus, Jordan; Becker, Jennifer; Geczi, Kristin; McKinnon, Sherry; Helsten, Dan L.; Sharma, Anshuman; Wildes, Troy S.; Avidan, Michael S.
Abstract : Background: Anesthesiologists need tools to accurately track postoperative outcomes. The accuracy of patient report in identifying a wide variety of postoperative complications after diverse surgical procedures has not previously been investigated. Methods: In this cohort study, 1, 578 adult surgical patients completed a survey at least 30 days after their procedure asking if they had experienced any of 18 complications while in the hospital after surgery. Patient responses were compared to the results of an automated electronic chart review and (for a random subset of 750 patients) to a manual chart review. Results from automated chart review were also compared to those from manual chart review. Forty-two randomly selected patients were contacted by telephone to explore reasons for discrepancies between patient report and manual chart review. Results: Comparisons between patient report, automated chart review, and manual chart review demonstrated poor-to-moderate positive agreement (range, 0 to 58%) and excellent negative agreement (range, 82 to 100%). Discordance between patient report and manual chart review was frequently explicable by patients reporting events that happened outside the time period of interest. Conclusions: Patient report can provide information about subjective experiences or events that happen after hospital discharge, but often yields different results from chart review for specific in-hospital complications. Effective in-hospital communication with patients and thoughtful survey design may increase the quality of patient-reported complication data. Abstract : In a study of over 1, 500 subjects more than 30 days after surgery, patient-reported outcomes, compared to automated or manual chart review, demonstrated poor-to-moderate positive agreement (0 to 58%) and excellent negative agreement (82 to 100%). Discrepancies frequently reflected patients reporting events that occurred outside the time period of interest, suggesting that more effective in-hospital communication and thoughtful survey design may improve the value of patient-reported outcomes.Supplemental Digital Content is available in the text.